Systematic studies of cryptocurrency usage tools for financial markets - Viktor Romanenko; Heorhii Kantsedal (Sistemnì Doslìdženâ ta Informacìjnì Tehnologìï)
The paper analyzes mining processes when using cryptocurrency on financial exchanges. It considers the cognitive map (CM) of the use of cryptocurrency as a complex system. It reveals all functions of mining processes when interacting with speculative instruments under conditions of uncertainties and risks. Digital modeling of impulse processes in the CM was carried out to study the dynamic properties of the free movement of the tops of the CM under random disturbances.